ANALISIS PENGARUH CITRA MEREK DAN KEPERCAYAAN MEREK TERHADAP MINAT BELI PADA PELANGGAN RITA PASARAYA CILACAP - Erna Dewi Tria; Toufan Aldian Syah (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2021)
This study aimed to analyze the effect of brand image and brand trust on customer purchase intention. The research uses a quantitative approach and descriptive analysis. Sampling using purposive sampling technique to obtain 60 observations. All statement instruments have passed the validity and reliability tests. The data analysis technique used multiple linear regression with classical assumption test as a prerequisite. Based on the analysis results, there is a significant influence between the brand image on customer buying interest. On the other hand, there is no significant effect between brand trust and customer buying interest. The F value indicates a significance level of 0.000, so the model is considered fit.